STUDI IMPLEMENTASI PERATURAN DAERAH TENTANG KAWASAN TANPA ROKOK (KTR) DI KOTA PALU - Putri, Puput (Ensiklopedia of Journal, 2025)
Tanpa Rokok/KTR) is an effort by the Palu City Government to create a healthy environment and protect the public from exposure to cigarette smoke. This study aims to examine the implementation of the KTR regulation in Palu City and to identify the factors that influence its effectiveness. The research employed a descriptive qualitative approach using data collection techniques such as in-depth interviews, observation, and documentation. Informants included representatives from the Health Office, Civil Service Police Unit (Satpol PP), public facility managers, and members of the community. The findings indicate that the implementation of the KTR regulation in Palu City has not yet been optimal. Based on George C. Edward III's policy implementation model, four key factors were identified: communication was not effective due to limited and uneven socialization efforts; resources were insufficient in terms of personnel, budget, and infrastructure; the disposition of implementers was generally supportive but lacked clear authority and guidance; and the bureaucratic structure was not well-integrated across sectors. Major challenges stemmed from weak inter-agency coordination, lack of supporting facilities, and limited public participation. This study recommends strengthening communication strategies, developing standard operating procedures (SOPs), establishing cross-sectoral implementation teams, increasing budget allocations, and actively involving the community to improve the effectiveness and sustainability of smoke-free area enforcement in Palu City.Keywords: Implementation, Smoke-Free Areas, Regional Regulation, George C. Edward III